Interpretation of groundwater hydrographs in the West Thessaly basin, Greece, using principal component analysis. - Σεφερλή, Σταματίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανικών Μεταλλείων Μεταλλουργών, 2016)
The scope of this work is to elucidate the use of Principal Components Analysis (PCA), a multivariate statistical procedure, as a tool to interpret the areal distribution of various types of water level fluctuation patterns within the watershed of Western Thessaly in Greece. In this area, intense ground water abstraction takes place during the last decades to cover the needs of agricultural activities, and is reported to have impacted significantly the ground water regime. For convenience, the study area was divided into three subareas, namely Farsala, Karditsa and Trikala, each of them containing a series of monitoring wells. In each of these areas, the water level variations for the past 40 years where examined thoroughly through plotted hydrographs. Then, PCA was applied in order to define a few uncorrelated linear combinations of the original hydrographs, which summarize the data set without losing much information. PCA revealed the existence of distinct temporal patterns in the available water level data, allowing the classification of wells into groups of similar behavior. The interpretation of the ground water level measurements with PCA can be used by the stake holders involved in ground water management (farmers, public authorities, general public, ecologists, etc.) to closely monitor the aquifers piezometry, through the identification of certain target wells from larger well groups. These target wells can be selectively measured in the long - term, allowing the sustainable monitoring and the collection of reliable ground level data.